Does representation of women in parliament promote economic growth? Considering evidence from Europe and Central Asia - Mirziyoyeva, Ziroat; Salahodjaev, Raufhon (Frontiers in Political Science, 2023)
Introduction The relationship between gender equality and economic growth has attracted considerable attention in scholarly research. While existing literature has evaluated the significance of gender inequality in education and employment, the impact of gender disparity in public service on economic growth remains an under examined area of scholarly inquiry. The main aim of this study is to assess the effect of female empowerment in public service on economic growth in Europe and Central Asia (ECA). To the best of our knowledge, this is the first analysis of the relationship between female political empowerment and economic growth at a regional level. Methods We rely on several econometric techniques to obtain robust empirical results and resolve various problems encountered when using panel data. We start with the random and fixed effects model to obtain the baseline results. The fixed effects model generates unbiased estimates by reducing the impact of time omitted variables. The core empirical technique used in this study is the twostep system GMM estimator. Results The empirical results suggest that female participation in parliament has a positive and significant effect on economic progress. In particular, a 10%-point increase in women's representation in parliament leads to a 0.74%-point increase in GDP growth. Discussion Thus, it is essential to further promote female empowerment programmes in developing countries and continue to adopt new measures aimed at increasing the participation of women in public service. Future studies could explore the relationship between female empowerment and economic growth at subnational levels and test whether female empowerment moderates the relationship between financial development, innovation, trade and economic growth.